Duobddága – homes and Sami sanctuaries - Aira, Harrieth (Sámi dieđalaš áigečála, 2022)
The sea and coastal culture are usually associated with coastal Sami areas, and the coastal Sami are connected to the sea. But in this article, we go ashore to the coastal Sami areas in Divtasvuodna (Tysfjord) on the Norwegian side of Sápmi. I wanted to find out more about the Sami people’s connections to the landscape, rather than exclusively focusing on their connections to the sea coast. I have studied what duobddága (the landscapes) mean to the Lule Sami and I have interviewed four persons from three different places about their traditions, practices, and beliefs.My study shows that the duobddága are of great importance for the Sami people. The duobddága are the summer settlements in the fjords where they live from spring to autumn, which are also their original settlements. The duobddága contribute to a sense of belonging and are the places of residence for families. These duobddága are also Sami majority communities in contrast to the winter settlements where the Sami are a minority. The duobddága are their homes, and the Sami maintain the connection to their summer settlements because they are important places for maintaining Sami identity, the Lule Sami language and culture.
Keywords: Tysfjord; Lule Sami; landscape; homes; practices